EDUCATIONAL REVOLUTION IN PROGRESS: REFLECTIONS ON STUDENTS, TEACHERS/TUTORS, AND DISTANCE LEARNING COURSES IN THE AI AGE - Liane Guarda de Farias, Daise (Revista Gênero e Interdisciplinaridade, 2025)
Education in the 21st century is undergoing a paradigmatic transformation driven by the integration of digital technologies and artificial intelligence, especially in distance education. In this context, the present research proposal had the general objective of reflecting on how these innovations transform pedagogical relationships, educational processes and distance learning courses. And, specifically: - to analyze how the student assumes a more autonomous and protagonist posture in the interaction with technological tools; and - to discuss how the role of the teacher/tutor and course planning should be adapted to enhance the use of these technologies. In carrying out this study, bibliographic research was used as a procedure to build a theoretical understanding of the topic addressed. It was concluded that the integration of Artificial Intelligence and emerging technologies in Distance Education not only transforms the roles of students and educators, but also redefines the very essence of teaching. By strengthening student autonomy and demanding new skills from teachers, distance learning becomes a dynamic platform that combines personalization and scalability with the essentiality of human interaction. Thus, at the end of this study, we hope to contribute to a deeper understanding of how emerging technologies, especially AI, are revolutionizing the distance education scenario.